Quality of life among diabetic retinopathy patients in Hospital Universiti Sains Malaysia - Latif, Noryani Abd. (Universiti Sains Malaysia, 2016)
Diabetic retinopathy can reduce the quality of life, it’s because this illness can cause blindness. The aim of this study was to determine the score vision related quality of life and its association with socio-demographic factors among diabetic retinopathy patients at the Ophthalmology Clinic at Hospital USM in Kubang Kerian, Kelantan. A total of 60 participants were selected in this study. It was a cross-sectional study. Evaluation of vision-related quality of life was using a 25 item National Eye Institute Visual Function Questionnaire (NEI VFQ-25). The data was obtained and analyzed using the Statistical Package for Social Sciences (SPSS) version 22.). The pearson correlation, "Independent t-test", and "One Way Anova" has been used for the association. The average overall score of VFQ-25 among diabetic retinopathy patients was 57.77. There was no association between the socio-demographic factors and vision-related quality of life of patients with diabetic retinopathy. End-stage complications have the greatest perceived burden on quality of life, but the early treatment diabetic retinopathy can improve wellbeing the quality of life. Overall, patients with diabetic retinopathy at Hospital USM is a moderate level with a composite scale (57.77).